Brain-Derived Neurotrophic Factor (BDNF) in Huntington’s Disease: Neurobiology and Therapeutic Potential - Azman, Khairunnuur Fairuz; Zakaria, Rahimah (Current Neuropharmacology, 2025)
Huntington's disease is a hereditary neurodegenerative disorder marked by severe neurodegeneration in the striatum and cortex. Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family of growth factors. It plays a crucial role in maintaining the survival and proper function of striatal neurons. Depletion of BDNF has been linked to impairment and death of striatal neurons, leading to the manifestation of motor, cognitive, and behavioral dysfunctions characteristic of Huntington's disease. This review highlights the current update on the neurobiology of BDNF in the pathogenesis of Huntington's disease. The molecular evidence and the affected signaling pathways are also discussed. In addition, the impact of experimental manipulation of BDNF levels and its pharmaceutical potential for Huntington's disease treatment are explicitly reviewed.
Keywords: neurodegeneration